Upaya Peningkatan Hasil Belajar Siswa Pada Mata pelajaran PAI di SD Negeri 29 Kampung Taji Melalui Model Pembelajaran PBL dengan Metode Card Sort - Sartika, Dwi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes and student engagement of fifth-grade students at SDN 29 Kampung Taji by implementing the Small Group Discussion method with the Problem-Based Learning (PBL) model in the lesson "Faith in the Hereafter." The study employed a Classroom Action Research (CAR) design consisting of two cycles, each comprising planning, implementation, observation, and reflection stages. The findings revealed that in Cycle I, the students’ learning mastery level reached only 60%, which increased to 80% in Cycle II. The average absorption rate also improved from 65.6% in Cycle I to a higher rate in Cycle II. Student engagement in learning activities significantly increased through small group discussions and the use of visual learning media. This study concludes that the Small Group Discussion method with the PBL model is effective in enhancing both learning outcomes and student engagement.